Effect of Gastrointestinal Hemorrhage on Outcome After Endovascular Treatment in Acute Basilar Artery Occlusion - Zhang, Hao; Dai, Weipeng; Kong, Weilin; Duan, Zhenhui; Yun, Zongjin; Zhou, Sheng; Yang, Jie; Li, Fengli; Zi, Wenjie; Guo, Zhangbao; Liu, Wenhua (Frontiers in Neurology, 2022)
Background and Purpose Gastrointestinal hemorrhage (GIH) is associated with a poorer prognosis and a higher mortality rate after acute ischemic stroke (AIS), but its association with outcomes after endovascular treatment (EVT) remains unclear. This study aimed to assess the incidence, risk factors, and relationships among clinical outcomes of GIH after EVT in patients with acute basilar artery occlusion (BAO). Methods Consecutive patients treated with EVT were identified from the EVT for Acute Basilar Artery Occlusion Study (BASILAR) registry. All enrolled patients were divided into GIH and non-GIH subgroups, and the independent predictors of GIH after EVT were explored. An ordinal logistic regression model was used to assess the association between GIH and primary outcome [distribution of modified Rankin scale (mRS)] at 90 days, while binary logistic regression models for other outcomes were also employed. Results Among 647 patients with acute BAO, 114 (17.6%) patients experienced GIH after EVT. Higher glucose levels at admission, longer procedure time, and general anesthesia were the independent predictors of GIH after EVT, while protective factors include the posterior circulation-Acute Stroke Prognosis Early Computed Tomography Score (pc-ASPECTS) ≥ 5 and a history of hyperlipidemia. Compared with the non-GIH group, the GIH group was associated with a worse functional outcome [adjusted common odds ratio (OR), 2.12 (95% CI, 1.39–3.25)], lower rates of functional independence [adjusted OR,.47 (95% CI, 0.26–0.88)], a favorable outcome [adjusted OR, 0.41 (95% CI, 0.22–0.73)], and a higher risk of 90-day mortality [adjusted OR, 1.76 (95% CI, 1.08–2.85)]. Conclusion This study concluded that GIH is not uncommon after EVT in patients with acute BAO and is associated with worse functional disability and higher mortality.